ANALYSIS OF EFFECTIVENESS AND EFFICIENCY IN BUDGET ABSORPTION - Sharaswati; Haliah; Nirwana (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Population and Registration Service Civil Buton Regency is element organizer affairs government area in the field administration population and registration civil being​ authority area . Budget shopping at the Population and Registration Service Civil Buton Regency sourced from Budget Regional Income and Expenditures (APBD). Budget provided​ must used in a way Good . If given budget​ No walk in a way effective and efficient so give rise to impact form use budget misdirected spending , overspending​​​ mark budget (overspending ) , shop below mark budget (underspending) , and violating purchases provision law (fraud spending) . Study This aim For analyze realization budget shopping to effectiveness and efficiency absorption budget shopping at the Population and Registration Service Civil Buton Regency . Research methods used​ is method descriptive quantitative . Research result This show that level effectiveness absorption budget shopping For 2016 effective​ of 98.98%, effective in 2017 of 92.65%, effective in 2018 of 95.12%, effective in 2019 amounting to 96.94%, and effective in 2020 amounting to 91.46%. Efficiency level absorption budget shopping For 2016 is very efficient amounting to 41.36%, in 2017 it was very efficient amounting to 47.32%, in 2018 it was very efficient amounting to 51.36%, in 2019 it was efficient amounted to 64.82%, and 2020 was very efficient of 58.85%